ETIKA DAN TANGGUNG JAWAB SOSIAL ILMUAN - . Maryati (Jurnal LEX SPECIALIS, 2010)
As a scientist must have a responsibility in every task he or she gain not only thet the result of his experiment must be filled with a responsibility to. This responsibility in a process of experiment is include in characteristic process. This process ia a morality that based on every etichs as a scientis like objective, open to critics and take the other opinion and dare toconfess his fault if that happen.   .Key Note :Responsibility and morality of scientist.